PROVISION OF SURGICAL SAFETY - V. M. Timerbulatov; Sh. V. Timerbulatov (Вестник хирургии имени И.И. Грекова)
OBJECTIVE. The research assessed the efficacy of WHO checklist for prevention of avoidable complications in surgery. MATERIALS AND METHODS. The article presents the results of implementation of WHO recommendations (checklist of measures) for prevention of so-called avoidable complications in surgery during performance of 35300 operations in 3-year period. The authors included two additional issues in the checklist about prevention of thromboembolic complications and temperature control in the operating unit. RESULTS. The number of preventable complications decreased in clinic after the implementation of WHO recommendations. The rate of thromboembolic and different postoperative complications also reduced in comparison with other clinic, where these recommendations haven’t been applied. CONCLUSIONS. The introduction of principles of prevention of complications in surgery according to WHO recommendations allowed significant decrease of the number of avoidable complications.